2014
DOI: 10.1158/1940-6207.capr-14-0273
|View full text |Cite
|
Sign up to set email alerts
|

Human Fecal Microbiome–Based Biomarkers for Colorectal Cancer

Abstract: Colorectal cancer may develop slowly over years from precursor lesions, and thus screening combined with early diagnosis is the key to disease prevention. Recent studies have elucidated specific traits in the gut microbiome associated with colorectal cancer and suggested that the microbiome may be useful in screening for colorectal cancer purposes but failed to provide protocols that can be applied in a practical situation. A recent study by Zackular and colleagues, presented on page 1112, provides an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…It is of interest since few or no report has been observed in literature. Interestingly, blood sample was obtained before colonoscopy and it is suggested that these microorganisms were able to achieve bloodstream through tumor tissue and they may remain in state of bacteremia for long period [6]. In this case, the infection in rectal cancer involves disruption of the normal barrier due to tumor-induced ulceration, followed by bloodstream invasion, in accordance with Mirza [7] Bacteremia caused by anaerobic bacteria represents from 0.5% to 12% of the total of bacteremia, and the mortality is approximately between 25% and 44% [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest since few or no report has been observed in literature. Interestingly, blood sample was obtained before colonoscopy and it is suggested that these microorganisms were able to achieve bloodstream through tumor tissue and they may remain in state of bacteremia for long period [6]. In this case, the infection in rectal cancer involves disruption of the normal barrier due to tumor-induced ulceration, followed by bloodstream invasion, in accordance with Mirza [7] Bacteremia caused by anaerobic bacteria represents from 0.5% to 12% of the total of bacteremia, and the mortality is approximately between 25% and 44% [8].…”
Section: Discussionmentioning
confidence: 99%
“…The best know example is the role Helicobater pylori plays in gastric cancer [43][44][45]. However, a handful of laboratories have reported links between bacterial infection and oral [11], colon [46][47][48][49], pancreatic [46,50], liver [51], esophageal [52] and prostate cancers [53]. The biological mechanism of these associations is not yet understood [54,55], however, there are several mechanisms by which bacterial infection could lead to the initiation and progression of oncogenic processes [42,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…However, oncobiome screening could potentially be designed to detect not only individual bacterial species associated with cancer but also dysbiosis long before adenomatous polyps or cancer have developed. Indeed a recent study characterized the microbiota from ‘healthy’ subjects and those with adenomas or CRC as confirmed by colonoscopy [51,131], and found that, when combined with known clinical risk factors for CRC (age, race, body mass index), combining six specific operational taxonomic units (OTU) of gut microbiota in stool samples significantly increased the ability to differentiate healthy subjects from those with adenomas or CRC. Likewise, taxonomic markers were identified through metagenomic sequencing of fecal samples to distinguish CRC patients from tumor-free patients [50].…”
Section: Have We Reached the Mirage?mentioning
confidence: 99%